Virtual enterprise collaborative processes monitoring through a project business approach - Shamsuzzoha, Ahm; Helo, Petri; Sandhu, Maqsood (Taylor & Francis, 2017)
In order to design a system for managing performance in collaborative project-based enterprises, it is necessary to undertake real-time monitoring of its business processes and activities. This paper presents a systematic approach to project business process monitoring (BPM) and identifies the key aspects of virtual enterprise (VE) process evaluation. A framework for VE BPM is presented with special emphasis in linking interest groups to the development of their targets, information and knowledge sharing. The proposed model defines the exclusive performance metrics, which are needed during BPM. This interdisciplinary study examines BPM through peer-to-peer information exchange in the VE domain, which is currently a research gap. The fundamental metrics to define business process performance monitoring are elaborated in the research reported in this paper. The identified performance metrics can be used to measure the overall performances for both a project business and VE. A reference architecture is also highlighted with a case example with the objective to measure the performance in a project business VE. An overall definition of collaborative BPM and performance management systems is also presented accordingly. Future research directions are identified regarding the nature of collaboration in a project business VE and the characteristics of performance indicators to support it.
Keywords: project business; virtual enterprise; process monitoring; information exchange; performance management; performance metrics and measurement; fi=Tuotantotalous|en=Industrial Management|